Functional And Structural Studies Of Alginate Lyase From Persicobacter sp. CCB-QB2 - Sim, Pei Fang (2017)
AlyQ gene from Persicobacter sp.CCB-QB2encodes alginate lyase which is comprised of two carbohydrate-bindingdomains, domains A and B,at the N-terminus of the alginate lyase domain, domain C. Alginate lyase domain from AlyQ belongs to the polysaccharide lyase 7 (PL7) family, while the first domain of the carbohydrate-bindingmodule resembles carbohydrate-bindingmodule 16 (CBM 16), and the second domain a CBM 32. Previous studies had mainly focused on activity characterization of alginate lyase or carbohydrate-binding modules individually but rarely on studies of the enzyme characteristics after combining these two domains and even less on the structural studies between alginate lyase and CBM domains. Therefore, this study focused on the alginate lyase enzymatic activity differences with or without the inclusion of the two carbohydrate-bindingdomains, and to elucidate the structural relationship between carbohydrate-bindingdomains and alginate lyase